Killing Thatcher: the IRA, the manhunt and the long war on the crown - Carroll, Rory (Mudlark, 2023)
A Sunday Times History Book of the Year 2023 A Spectator Book of the Year 2023 The Irish Times No.1 Bestseller As taut as a fictional thriller Mail on Sunday Gripping, detailed and richly layered Guardian KILLING THATCHER is the gripping account of how the IRA came astonishingly close to killing Margaret Thatcher and to wiping out the British Cabinet - an extraordinary assassination attempt linked to the Northern Ireland Troubles and the most daring conspiracy against the Crown since the Gunpowder Plot. In this fascinating and compelling book, veteran journalist Rory Carroll retraces the road to the infamous Brighton bombing in 1984 - an incident that shaped the political landscape in the UK for decades to come. He begins with the infamous execution of Lord Mountbatten in 1979 - for which the IRA took full responsibility - before tracing the rise of Margaret Thatcher, her response to the Troubles in Ireland and the chain of events that culminated in the hunger strikes of 1981 and the death of 10 republican prisoners, including Bobby Sands. From that moment on Thatcher became an enemy of the IRA - and the organisation swore revenge. Opening with a brilliantly-paced prologue that introduces bomber Patrick Magee in the build up to the incident, Carroll sets out to deftly explore the intrigue before and after the assassination attempt - with the story spanning three continents, from pubs and palaces, safe houses and interrogation rooms, hotels and barracks. On one side, an elite IRA team aided by a renegade priest, US-raised funds and Libyas Qaddafi and on the other, intelligence officers, police detectives, informers and bomb disposal officers. An exciting narrative that blends true crime with political history, this is the first major book to investigate the Brighton attack